Efektivitas Formula Biofungisida dalam Mengendalikan Penyakit Layu Fusarium pada Tanaman Cabai (Capsicum annuum L.) - PURBA, DEA NATALIA KARO; KHALIMI, KHAMDAN; SUNITI, NI WAYAN (Agrotrop : Journal on Agriculture Science, 2023)
The Effectiveness of the Biofungicide Formula in Controlling Fusarium Wilt Disease in Chili Plants ( Capsicum Annuum L.) . Fusarium oxysporum f.sp. capsici is one of the pathogenic fungi that causes Fusarium wilt disease in chili plants. This disease can be suppressed by Gliocladium sp. as a biological agent that can be used as an active ingredient in biofungicide formulas. Biofungicide is the use of biological agents as active ingredients combined with natural carrier agents to form a biofungicide formula. The purpose of this study was to determine the effect and the best effective dose of the formula Gliocladium sp. in controlling wilt disease caused by F. oxysporum f.sp. capsici. The results of the inhibitory test of Gliocladium sp. against F. oxysporum f.sp. capsici in vitro showed that Gliocladium sp. was able to inhibit the growth of the fungus F. oxysporum f.sp. capsici with an inhibitory percentage of 98.96 when compared to the control. The results of the test of the effectiveness of the biofungicide formula in controlling wilt disease in vivo showed that the biofungicide formula at a dose of 2 grams per plant was able to reduce the percentage of fusarium wilt from 100% to 0%.